Study of the Effect of Withdrawal Rate on Polyethylene Tereftalat (PET) Filaments from Plastic Bottle Waste for 3D Printing Applications - Mahfudh, Lauqhi
Plastic waste is still problem for many people because it takes a long time to unravel. One of the massive amounts of plastic waste is plastic bottles. Based on data from Sustainable Waste Indonesia funded by Danone Aqua, as many as 350,000 tons of plastic bottle waste are produced annually. By using 3D printing technology in the recycling process, it can not only reduce the amount of waste but also increase the value of the product resulting from the recycling process. In previous studies, 3D printing filaments based on PET have been successfully made but have a problem, the resulting filaments are brittle. In this study, PET plastic that was mechanically recycled was extruded with a filament withdrawal rate of 35 mm/s, 40mm/s, and 45 mm/s. In the extrusion process, the resulting filament has varying average diameters, the largest average filament diameter obtained is 1.28 mm on the x-axis and 0.95 mm on the y-axis. The faster the withdrawal rate, the smaller the diameter of the 3D printing filament obtained. 3D printing objects made from PET filaments have an accuracy that is not too much different from 3D printing filaments sold in the market, such as PLA and ABS. This shows that PET plastic bottles have the potential to be recycled into 3D printing filaments.